Transformasi Digital Layanan Perizinan Publik di Kabupaten Sintang, Kalimantan Barat - Nur, Utami; Pratiwi, Dita (Faculty of Social and Political Science, 2025)
Technological advancements and globalization have driven the transformation of public services through e-Government, including the digitalization of business licensing in Indonesia via the Online Single Submission (OSS) system. OSS aims to integrate licensing services across ministries, agencies, and local governments; however, its implementation faces challenges such as limited digital literacy, uneven network infrastructure, and geographic constraints, particularly in remote areas. This study examines the transformation of OSS in Sintang Regency, from its initial implementation to the broader context of improved service access, with the Mall Pelayanan Publik (MPP) mentioned as a supporting facility. A qualitative case study approach was employed using secondary data, including regulations, OSS implementation documents, DPMPTSP Sintang performance reports, and relevant literature. Data were analyzed using the interactive model of Miles, Huberman, and Saldana. Findings indicate that OSS transformation progressively enhances service quality and user satisfaction, supported by organizational capacity, clear SOPs, and staff training, demonstrating an adaptive model bridging social, technical, and geographic gaps in digital public services.